2000
DOI: 10.1067/mva.2000.105961
|View full text |Cite
|
Sign up to set email alerts
|

Interposition vein cuff anastomosis alters wall shear stress distribution in the recipient artery

Abstract: The vein cuff anastomosis alters the mean WSS distribution within the recipient artery and removes the area of low WSS at the heel. This may explain the redistribution of MIH away from important sites in the recipient artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…16 Likewise, the myointimal hyperplasia inside the anastomosis preferentially occurs at the region of low wall shear stress, including the heel, toe, and floor of the recipient artery, thus implicating an inverse relationship between the force and myointimal hyperplasia. 1,2,14,17 The results of the present study indicated that the flow behavior inside the distal anastomosis is affected by the inlet flow velocity profile and the flow split ratio. Because the reflection component of the flow velocity waveform tends to disappear with the increased numbers of ligated popliteal tributaries, there seems to be an inverse correlation between the peripheral vascular resistance and the depth of the negative reflection component.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…16 Likewise, the myointimal hyperplasia inside the anastomosis preferentially occurs at the region of low wall shear stress, including the heel, toe, and floor of the recipient artery, thus implicating an inverse relationship between the force and myointimal hyperplasia. 1,2,14,17 The results of the present study indicated that the flow behavior inside the distal anastomosis is affected by the inlet flow velocity profile and the flow split ratio. Because the reflection component of the flow velocity waveform tends to disappear with the increased numbers of ligated popliteal tributaries, there seems to be an inverse correlation between the peripheral vascular resistance and the depth of the negative reflection component.…”
Section: Discussionmentioning
confidence: 88%
“…1 A distal anastomotic cuff may improve the patency, thereby relocating or inhibiting the accretion of hyperplasia. 2,3 The mechanical properties of the cuff are not necessarily involved in such an improvement, 4 but adaptation of the flow patterns to reduce low wall shear stress areas along the recipient arterial floor has been hypothesized to be the main mechanism. 2 In recent computational fluid dynamics studies, however, conflicting views have been reported about the hemodynamic benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,32,34 Others argued for the better hemodynamics produced by the unique cuff geometry. 5,9,11 They pointed out that the cuff geometry engenders a characteristic vortical flow structure which enhances mixing within the cuff to produce a wash-out effect in the cuff cavity, and reduces area of low flow and flow separation along the native artery, thereby increasing wall shear stress (WSS) at critical sites (e.g. toe, heel and floor of the host artery).…”
Section: Introductionmentioning
confidence: 99%
“…2) The geometry of the anastomosis is an important determinant of flow patterns and WSS distribution. 3) It has been shown that the angle of an end-to-side (ETS) anastomosis can affect the local flow pattern. [4][5][6] In vitro studies have also demonstrated altered flow patterns in ETS anastomoses with a patent proximal outflow segment.…”
mentioning
confidence: 99%